Pengaruh Sistem Human Resource Development (HRD) Terhadap Peningkatan Kinerja Karyawan Pada PT. Bank Syariah Indonesia Stabat - Ardiansyah Putra; Sri Wahyuni (Lembaga Riset Ilmiah, 2022)
This study aims to determine the effect of implementing the Human Resource Development (HRD) system on improving employee performance at PT. Bank Syariah Indonesia, Tbk KCP Stabat. This type of research is quantitative research. Methods of collecting data from data sources obtained through questionnaire answers given by research respondents, namely all employees at PT. Bank Syariah Indonesia, Tbk KCP Stabat. The data analysis technique used the stages of validity testing, reliability testing, normality testing, hypothesis testing, and multiple linear regression analysis. The results of the study show that the implementation of the Human Resource Development (HRD) system has a significant effect on improving employee performance at PT. Bank Syariah Indonesia, Tbk KCP Stabat. This is obtained through the results of hypothesis testing, namely the t test which shows a significant value less than 0.05 or (0.00 < 0.05) and t count > t table (4.563 > 2.10092) then there is an effect of variable X on Variable Y. The implementation of the Human Resource Development (HRD) system by PT. Bank Syariah Indonesia, Tbk KCP Stabat affect the increase in employee performance by 51.1%. There is a positive or consistent relationship between the implementation of the Human Resource Development (HRD) system and the improvement of employee performance, the better the implementation of the Human Resource Development (HRD) system by PT. Bank Syariah Indonesia, Tbk KCP Stabat, the increase in employee performance is also getting better, and vice versa if the implementation of the Human Resource Development (HRD) system by PT. Bank Syariah Indonesia, Tbk KCP If the stabat is bad, the employee's performance will also decrease